Decreased Colonic Guanylin/Uroguanylin Expression and Dried Stool Property in Mice With Social Defeat Stress - Ebisutani, Nobuhiko; Fukui, Hirokazu; Nishimura, Heihachiro; Nakanishi, Takashi; Morimoto, Kenki; Itou, Shiho; Nakamura, Ayumi; Masutani, Mizuki; Hori, Mika; Tomita, Toshihiko; Oshima, Tadayuki; Kasahara, Emiko; et al. (Frontiers in Physiology, 2020)
Psychological stress is deeply involved in the pathophysiology of not only mental illness but also functional gastrointestinal disorders. In the present study, we examined the relationship between psychological stress and abnormality of stool properties, focusing on the alteration of plasma glucocorticoid and guanylin (GN)/uroguanylin (UGN) expression in the colon. A murine model of chronic social defeat stress (CSDS) was established by exposing a C57BL/6N intruder mouse to a CD-1 aggressor mouse for 3-5 min. Thereafter the mice were kept in the same cage but separated by a divider for the remainder of the day. This procedure was repeated for 10 consecutive days, and then a social interaction test was performed to evaluate social avoidance. Fresh fecal and blood samples were collected for stool property analysis and measurement of the plasma glucocorticoid level by ELISA. The expression of GN, UGN and guanylate cyclase 2C (GC-C) in the colonic tissues was examined by real-time RT-PCR and immunohistochemistry. Moreover, Lovo cells were stimulated with dexamethasone, and the expression of GN/UGN mRNA was examined. In the CSDS group, the time spent in the social interaction zone was significantly shorter when the CD-1 aggressor mouse was present than when it was absent. The social interaction ratio was also significantly lower in the CSDS group relative to the controls. The mean Bristol scale score was significantly lower in the CSDS group, but the fecal sodium concentration did not differ between CSDS mice and controls. The level of plasma corticosterone was significantly higher in the CSDS group than in the controls immediately after the 10th day of CSDS. The expression of both GN and UGN was significantly decreased in the CSDS mice. GN was expressed in all colonic epithelial cells, and UGN was expressed in ovoid or pyramidal epithelial cells in the colonic mucosa. The expression of both GN and UGN was significantly decreased in the CSDS mice relative to controls. The expression of both GN and UGN was significantly suppressed in Lovo cells upon stimulation with dexamethasone. Psychological stress-induced glucocorticoid may suppress colonic GN/UGN expression, resulting in a change in stool properties leading to constipation.